2017
DOI: 10.1101/136259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How sample size influences the replicability of task-based fMRI

Abstract: Despite a growing body of research suggesting that task-based functional magnetic resonance imaging (fMRI) studies often suffer from a lack of statistical power due to too-small samples, the proliferation of such underpowered studies continues unabated. Using large independent samples across eleven distinct tasks, we demonstrate the impact of sample size on replicability, assessed at different levels of analysis relevant to fMRI researchers. We find that the degree of replicability for typical sample sizes is … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Still, Paul et al demonstrated recently that even large fMRI studies (i.e. N = 100) do not produce group results with good reliability (Paul, Turner, Miller, & Barbey, 2017). Furthermore, previous studies showed that group-level stability is not indicative of individual stability (Raemaekers et al, 2007;van den Bulk et al, 2013;Vetter, Pilhatsch, Weigelt, Ripke, & Smolka, 2015), while research focusing on within-subject reliability over time has produced mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Still, Paul et al demonstrated recently that even large fMRI studies (i.e. N = 100) do not produce group results with good reliability (Paul, Turner, Miller, & Barbey, 2017). Furthermore, previous studies showed that group-level stability is not indicative of individual stability (Raemaekers et al, 2007;van den Bulk et al, 2013;Vetter, Pilhatsch, Weigelt, Ripke, & Smolka, 2015), while research focusing on within-subject reliability over time has produced mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Our study has four main limitations. First, the sample size (n = 13) is relatively small, compared to the recommendations for a typical task-based FMRI study (n = 30;Turner et al, 2018). Our sample size was not based on a formal sample size calculation because we were unable to find effect sizes for an FMRI experiment similar to ours.…”
Section: Methodological Considerationsmentioning
confidence: 92%
“…For generalizability considerations, there should also be a floor for both subject and trial sample sizes as a rule of thumb. Various recommendations have been proposed for the minimum number of subjects, ranging (at present) from 20 (Thirion et al, 2007) to 100 (Turner et al, 2018); these numbers are likely to depend strongly on experimental design, tasks, region(s) of interest and other specific considerations. Similarly, no single minimum number of trials can be recommended across all studies, for the same reasons.…”
Section: Beyond Efficiency: Trial Counts For Generalizability Replicability Power and Reliabilitymentioning
confidence: 99%